The impact of antibiotic exposure on antibiotic resistance gene dynamics in the gut microbiota of inflammatory bowel disease patients - Zhang, Yufei; Xue, Gaogao; Wang, Fan; Zhang, Jing; Xu, Lida; Yu, Changyuan (Frontiers in Microbiology, 2024)
While antibiotics are commonly used to treat inflammatory bowel disease (IBD), their widespread application can disturb the gut microbiota and foster the emergence and spread of antibiotic resistance. However, the dynamic changes to the human gut microbiota and direction of resistance gene transmission under antibiotic effects have not been clearly elucidated. We analyzed 90 fecal samples collected from 30 IBD patients before, during and after antibiotic treatment through metagenomic analysis to describe bacterial community and resistance gene changes over time. We found that exposure to antibiotics induced alterations to the gut microbiota composition, particularly reducing probiotics and increasing network complexity, which gradually recovered to a new steady state after cessation.We explored consistent relationships between the gut microbiota and resistome, and established gene transmission networks pre-treatment and post-treatment. We found that Enterobacteriaceae and Pseudomonadaceae harboring the most antibiotics resistance genes (ARGs). ARGs transfer was more prevalent among Firmicutes, Enterobacteriaceae and Pseudomonadaceae. The vanH gene associated with glycopeptide resistance was widely transferred among most individuals. The findings provide ecological insight into resistance gene dynamics and dissemination upon antibiotic perturbation of the microbiota, highlighting optimization of antibiotic usage to limit unintended resistance increases in gut bacteria during IBD management.